Effect of low cost fillers on cement hydration. (15th October 2016) - Choudhary, Antara; Shah, Vineet; Bishnoi, Shashank
Highlights: Compressive strength similar to OPC was obtained by replacing cement with coarser materials. Improved cement hydration rate due to more nucleation sites and autocatalytic effect of seeds. Using hydrated cement as fillers gives similar compressive strength while reducing the cost. Abstract: The beneficial use of industrial, construction & demolition waste would solve the severe problem of their disposal being faced today. This study aims to overcome this challenge by utilizing these wastes in concrete as fillers and seeds to enhance strength and accelerate hydration. The compressive strength and rate of hydration of blends with partial replacement of cement by fillers; marble dust, rutile; and crushed hydrated cement seeds were studied. The results revealed the effectiveness of marble dust as a filler improving both compressive strength and rate of strength gain. The cement seeds proved to be effective with even at low replacement levels leading to equivalent strength and hydration rate of both pure and fly ash blended cements.